The Stability of Money Demand Function: Evidence from South Africa - Omar, Farhan Abdi; Hussein, Abdishakur Mohamed (International Journal of Economics and Financial Issues, 2020)
The main purpose of this paper is to assess whether the Money Demand Function is stable in South Africa by employing the Johansen co-integration and the Vector Error Correction Model (VECM). The results indicate unstable money demand function among its determinant including real income, interest rate, stock price, and real exchange rate. More importantly, the M3 has a significant long-run relationship among its determinant except the interest rate. Furthermore, the short term dynamics show that unidirectional causality runs from determinants to the broader money except interest rate and exchange rate. This paper provides crucial evidence for policy-makers to consider the importance of the stock market activity to avoid misspecification of the money demand function. Keywords: Money demand, Johansen, VECM, Stock price. JEL Classifications: E5, E41 DOI: https://doi.org/10.32479/ijefi.9799